Deletion analysis of DMD/BMD families from the German Democratic Republic and selected regions of Czechoslovakia and Hungary. Issue 11 (November 1990) - Speer, A; Kräft, U; Hanke, R; Grade, K; Coutelle, C; Wulff, K; Wehnert, M; Herrmann, F H; Kadasi, L; Kunert, E
Abstract : Over the last two years we have screened 183 DMD/BMD families requesting prenatal diagnosis. Using cDNA probes cf56a, b we have detected exon deletions in 72 of them. In 62 cases the deletion was also detectable with currently available PCR primers. Deletion analysis for exons 8, 17, and 19, using either PCR or Southern blotting techniques, was performed for 65 of the 111 families which showed no deletions with cf56a, b. Eight of them were deleted for one or more of these exons. PCR offers new possibilities for deletion analysis in families without a living patient using either Guthrie papers or histologically conserved material from the dead patient. In 20 of 25 patients, we observed concordance between the clinical picture and the molecular deletion analysis in accordance with the open reading frame hypothesis. Five patients, however, presented with DMD in spite of our analysis showing an in frame deletion. Carrier determination in families in which DMD is caused by a deletion using linkage, dosage, or breakpoint analysis is discussed.